Glycoconjugates and Related Molecules in Human Vascular Endothelial Cells - Norihiko Sasaki; Masashi Toyoda (International Journal of Vascular Medicine)
Vascular endothelial cells (ECs) form the inner lining of blood vessels. They are critically involved in many physiological functions, including control of vasomotor tone, blood cell trafficking, hemostatic balance, permeability, proliferation, survival, and immunity. It is considered that impairment of EC functions leads to the development of vascular diseases. The carbohydrate antigens carried by glycoconjugates (e.g., glycoproteins, glycosphingolipids, and proteoglycans) mainly present on the cell surface serve not only as marker molecules but also as functional molecules. Recent studies have revealed that the carbohydrate composition of the EC surface is critical for these cells to perform their physiological functions. In this paper, we consider the expression and functional roles of endogenous glycoconjugates and related molecules (galectins and glycan-degrading enzymes) in human ECs.